2013
DOI: 10.1039/c3mt20262c
|View full text |Cite
|
Sign up to set email alerts
|

PtCl2(phen) disrupts the metal ions binding to amyloid-β peptide

Abstract: Platinum phenanthroline complexes have been found to inhibit Aβ aggregation and reduce Aβ caused neurotoxicity. Our previous results revealed the synergistic roles of phenanthroline ligand and Pt(ii) coordination in the inhibition of Aβ aggregation. In this work, the reactions of PtCl2(phen) with metal bound Aβ complexes were investigated. HPLC results show that the copper coordination decreases the reaction rate of PtCl2(phen) with Aβ1-16 and influences the distribution of products on HPLC profiles. EPR resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 48 publications
(250 reference statements)
2
27
0
Order By: Relevance
“…LFMM is a powerful modelling tool for the study of transition metal complexes and has previously found success in predicting their interactions with biomolecules. In this work, we apply the LFMM approach to a series of six Pt II complexes -as studied by Barnham 16,17,45 and others 19,20,21 -and their interaction with model fragments of the amyloid-β peptide in order to determine favourable metal binding modes as well as their influence on peptide secondary structure. Conformational space of Aβ was explored using δowεode εD with AεBER molecular mechanics parameters, followed by further optimisation using the semi-empirical PM7 method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LFMM is a powerful modelling tool for the study of transition metal complexes and has previously found success in predicting their interactions with biomolecules. In this work, we apply the LFMM approach to a series of six Pt II complexes -as studied by Barnham 16,17,45 and others 19,20,21 -and their interaction with model fragments of the amyloid-β peptide in order to determine favourable metal binding modes as well as their influence on peptide secondary structure. Conformational space of Aβ was explored using δowεode εD with AεBER molecular mechanics parameters, followed by further optimisation using the semi-empirical PM7 method.…”
Section: Discussionmentioning
confidence: 99%
“…However, characterization of these Pt II (ligand)-Aβ complexes is difficult, with authors suggesting a variety of different metal binding modes 16,19,20 . Experimental evidence indicates that a series of platinated adducts are formed when Pt II (phenanthroline) complexes bind to Aβ, though the N-terminal His6 and His14 residues are the most common Pt II binding sites 16,19,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The results are still contradictory but represent a significant contribution to the better understanding of these processes. 238 The Pt(II) induced rearrangement of Cu(II) coordination sites was reported in another study too, but the ROS production was not influenced. 210 The same technique was also applied to understand the effect of the metal ions on the misfolding and aggregation of the peptide.…”
Section: Thermodynamic Kinetic and Structural Studies On The Metal Cmentioning
confidence: 80%
“…Firstly, the peptide fragment will be extended to at least the Aβ1-16 unit studied in experimental work 19,54 . This would allow confirmation of platinum binding modes on a more realistic model of biological Aβ.…”
Section: Discussionmentioning
confidence: 99%